Penerapan Metode Rapid Application Development Dan Weighted Moving Average Pada Sistem Informasi Peramalan Persediaan Berbasis Web - Hidayatulloh, Akhmat; Tanuwijaya, Haryanto; Hananto, Valentinus Roby (STMIK Banjarbaru, 2024)
Business competition has caused inventory problems at UDRJ, a trading company with sales coverage throughout East Java. UDRJ requires an inventory forecasting information system for overcoming these problems. The aim of this research is to apply the Rapid Application Development and Weighted Moving Average methods to the web-based inventory forecasting information system at UDRJ. The Weighted Moving Average method was chosen because the data is time-series and this method is responsive in predicting changes in market trends. The information system was developed on a web basis considering the ease of data access, low costs and ease of system maintenance. The information system development stages in this research use the Rapid Application Development method because it has a shorter life cycle and allows more flexible solution design and implementation. This research produces a web-based inventory forecasting information system with a forecasting accuracy rate of 85.45% and good performance as evidenced by a MAPE of 14.54%. The application of the Weighted Moving Average method was able to increase forecasting accuracy by 18.18% so that it was implemented appropriately according to the company's needs.Keyword: Weighted Moving Average; Rapid Application Development; Forecasting Information System; Stock; Web-based Â AbstrakPersaingan bisnis yang ketat telah menimbulkan permasalahan persediaan di UDRJ, perusahaan perdagangan dengan jangkauan penjualan di seluruh Jawa Timur. Untuk mengatasi permasalahan tersebut UDRJ membutuhkan sistem informasi peramalan persediaan. Tujuan penelitian ini adalah menerapkan metode Rapid Application Development dan Weighted Moving Average pada sistem informasi peramalan persediaan berbasis web di UDRJ. Metode Weighted Moving Average dipilih karena data bersifat time-series dan metode ini responsif dalam memrediksi perubahan tren pasar. Sistem informasi dikembangkan berbasis web mengingat kemudahan akses data, biaya rendah, dan kemudahan pemeliharaan sistem. Tahapan pengembangan sistem informasi dalam penelitian ini menggunakan metode Rapid Application Development karena memiliki daur hidup lebih singkat dan memungkinkan perancangan dan implementasi solusi lebih fleksibel. Penelitian ini menghasilkan sistem informasi peramalan persediaan berbasis web dengan tingkat akurasi peramalan 85,45% dan berkinerja baik yang dibuktikan dengan MAPE sebesar 14,54%. Penerapan metode Weighted Moving Average mampu meningkatkan akurasi peramalan sebesar 18,18% sehingga sudah tepat diterapkan sesuai kebutuhan perusahaan. Â Â